Chemical and physical processes controlling the distribution of aerosols in the Lower Fraser Valley, Canada, during the Pacific 2001 field campaign - Boudries, H; Canagaratna, M. R.; Jayne, J. T.; Alfarra, M. R.; Allan, J; Bower, KN; Coe, H.; Pryor, SC; Jimenez, J. L.; Brook, J. R.; S Li,; Worsnop, D. R. (ATMOSPHERIC ENVIRONMENT, 2004)
High-resolution size-resolved mass concentration of organic and inorganic species present in/on sub-micron particles measured during the PACIFIC 2001 field study in the Lower Fraser Valley (LFV) are presented. The measurements of major particulate species (organics, sulfate, nitrate and ammonium) were made in situ and in real time at three different sites representing urban (Slocan Park), semi-rural (Sumas) and rural (Langley) areas, using two Aerodyne aerosol mass spectrometers (AMSs). The total non-refractory PM1.0 mass concentrations at the three sites were found to range from 0.12 to 24.50 mug m(-3), with an average concentration of 4.76 mug m(-3.) A large variability in aerosol composition was observed in the LFV, depending on meteorological conditions. Generally, during southwesterly wind conditions, inorganic species accounted for 50% of total mass loadings in the LFV, while during stagnant conditions organic species made up the majority of the particle mass. The organic aerosol species exhibit a bimodal size distribution, while the inorganic species are in most cases confined to the accumulation mode centered around 400 nm. Background sulfate levels of similar to 1 mug m(-3) were observed in the LFV during the entire campaign. Transport is found to be an important factor controlling the composition of sulfate in the LFV. Several photochemical events leading to the observation of substantial increases of sulfate in the LFV were also identified. Many of these events involve sulfate-dominated growth of small particles and appear to occur on a regional scale within the LFV. (C) 2004 Elsevier Ltd. All rights reserved.